La Enfermería en México en el Ambiente Prehospitalario: Oportunidades y Retos para la Atención de Emergencias - Paola Glafisbel Ramírez Torres; Gabriela Hernández Morales (Ibero Ciencias - Revista Científica y Académica - ISSN 3072-7197, 2026)
The purpose of this research is to analyze the role of nursing in the prehospital setting in Mexico, identifying the challenges faced by healthcare personnel in emergency care and exploring opportunities to strengthen their interventions. This article arises from the need to recognize the importance of nursing as a fundamental link in the chain of timely medical care, especially in emergency situations where a rapid and effective response can mean the difference between life and death.